Hybrid electronic skin combining triboelectric nanogenerator and humidity sensor for contact and non-contact sensing. (October 2022) - Yin, Feifei; Guo, Yunjian; Qiu, Zhicheng; Niu, Hongsen; Wang, Wenxiao; Li, Yang; Kim, Eun Seong; Kim, Nam Young
Abstract: Developing an electronic skin (e-skin) by mimicking a human skin sensory system in which tactile sensing and non-contact sensing complement each is of great significance for helping wearable electronic products to realize the intelligent perception of contact and non-contact information. Here, a hybrid e-skin (CNES) that realizes both contact and non-contact sensing is reported, which consists of a triboelectric nanogenerator (TENG) and a humidity sensor that share a flexible substrate layer. The shared flexible substrate is formed by a hydrothermal method and presents a porous and nanoflake-like morphology surface. By introducing an Ag nanowires (NWs) electrification layer on the upper surface of the shared substrate, CNES exhibits advantages in contact sensing and electrical output performance. Therefore, we achieve the monitoring for falling behaviors with such a CNES serving as a contact sensor and the management of humidity management system with the matrixes of CNESs simulating the self-powered switches. In addition, the SnO2 humidity sensing layer that is introduced on the lower surface of the shared substrate facilitates the CNES to achieve the non-contact monitoring of human respiration signals, offering a reliable pathway to design electronic skin for both contact and non-contact sensing. Graphical Abstract: ga1 Highlights: A shared flexible substrate is proposed by etching Al foil via a hydrothermal method. Ag NWs electrification layer endows CNES with superior contact sensing capability. SnO2 humidity layer helps CNES exhibit an excellent non-contact sensing performance. CNES provides an opportunity to build complementary contact and non-contact e-skins.